Coordinating Words and Sentences: Detecting Age-Related Changes in Language Production. - Jee Eun Sung; Eunha Jo; Sujin Choi; Jiyeon Lee (Journal of Speech, Language & Hearing Research, 2024)
Purpose: The purpose of this study was to examine whether older adults exhibit reduced abilities in coordinating lexical retrieval and syntactic formulation during sentence production and whether an individual’s working memory capacity predicts age-related changes in sentence production. Method: A total of 124 Korean-speaking individuals (79 young and 45 older adults) completed a lexical priming sentence production task. The participants described a target picture (a dog biting a monkey) after reading either an agent (dog) or a theme (monkey) prime word. The proportion of passive sentences was used as the dependent variable. Results: When the theme noun was primed, older adults produced fewer passive sentences than young adults. Working memory tasks significantly predicted individual differences in the sentence production of older adults. Conclusions: With aging, the ability to efficiently formulate syntactic structures in coordination with varying lexical information declines. Among older adults, age-related changes in these sentence production processes are associated with reduced working memory. Our constrained language production task is sensitive to detecting aging effects.